O jogar e o funcionamento cognitivo do sujeito surdo - Chaves, Hamilton Viana (2011)
The research presented in this thesis was based on three major fields of study: the mediational and cognitive processes involved in teaching and learning situations, the games as play activity, and deafness. From this entanglement there was the attempt to investigate how the cognitive functioning of deaf people would happen while they were building knowledge mediated by learning games. The aim is to understand the cognitive functioning of deaf subjects when in teaching and learning situations that were aided by games, to this end, we analyzed the language productions of deaf people in interaction resulting from processes of teaching and learning facilitated by games; the genesis of the processes of knowledge construction was described taking into account its constant pragmatic (sensorimotor) and formal (conceptual), and an explanatory summary was formulated about the formation of meanings emerged through processes of teaching and learning facilitated by games. The survey was conducted with deaf students from Instituto Cearense de Educação de Surdos and from Centro de Capacitação de Profissionais da Educação e Atendimento às Pessoas com Surdez, both in the city of Fortaleza-CE. During part of 2009 and 2010 learning activities mediated by games were filmed to constitute the corpus for further analysis. The analytics followed the microgenetic model proposed by Heinz Werner and Lev Vygotski. Five episodes were chosen based on which ones would be most enlightening and according to the starting question for the execution of the study. It was found that imaginative thinking, information exchange, sharing of feelings were decisively influenced by the body experience of the subjects. Regarding the field of mathematical and logical thinking, it was observed that thought experiment was an important resource used by deaf students in problem-solving strategies. The findings indicated that the course of cognitive functioning of subjects was decisively undermined by the set of body experiences arising from their daily interactions licensed by the use of sign languages.